Performance analysis of single and multi-controller using openFlow protocol for softwareDefined networks - Khalil Al Dulaimi, L.A.; Badlishah Ahmad, R.; Yaakob, N.; Ahmed, I.S.; Elshaikh, M. (2018)
A Software Defined Network (SDN) is a relatively advanced way to implement communication networks. The decision making SDN separates the control layer, which determines where the packets are sent, from the basic infrastructure (also known as the infrastructure layer or data plan) which restores the packets to the specified destination. The newly emerging standard for enactment is the OpenFlow protocol, which contains a standard protocol for communications between the control layer and the infrastructure layer. This study analyzes the impact of OpenFlow single and multi-controllers on the performance of the OpenFlow protocol network. The research was conducted using the discrete event network simulation, omnet++, and involved analyzing the main network metrics including End to End Delay and Throughput. The results indicate that the type of controller used has a clear impact on the performance of the network.